STABILITAS EKONOMI DAN NILAI TUKAR INDONESIA: PERPEKTIF KEBIJAKAN FISKAL DAN MONETER ISLAM - Febrianto, M. Nanang; Mashudi, Mashudi; Asiyah, Binti Nur (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
Fiscal deficit policy during a recession can be used as a stimulus to encourage economic growth, but in the long term, deficits financed by foreign debt can cause economic instability and increase the risk of inflation and increased interest burdens. The Purpose of the study determine the role of Islamic fiscal and monetary policy in maintaining stable economic growth and exchange rates. The research method was carried out qualitatively using a literature study approach sourced from various books, journals, and government agency reports. The results obtained show that when a recession occurs the government encourages economic growth through a fiscal deficit funded through foreign debt which has a long-term impact on increasing the debt and interest burden. In Islam there are alternatives using cash Waqf and the issuance of State Sharia Securities which have an impact on long-term economic stability and ZIS which can help reduce poverty and inequality. Meanwhile, monetary policy aims to influence the circulation of money, increase employment opportunities, exchange rate stability and purchasing power through sharia-based instruments that don’t use elements of usury through Statutory Reserve Requirements, Financial Ceilling, Moral Suasion, Profit and Sharing Ratio, Sukuk.